Are industrial parks in Korea evolving? Or are they just aging?. Issue 1 (2nd January 2018) - Song, Ji-Hyun
ABSTRACT: This study investigates how the age of industrial parks may affect their tenants' performance, to find ways to enhance the positive effects of industrial parks and the efficiency of their regeneration. We identify a relationship between the parks' age and tenants' performance. Further, we estimate changes in tenant performance against the age of the park. The analysis is based on firm-level data of 1812 small- and medium-sized manufacturing firms with only one factory in any given industrial park in 2016. The important findings that can be drawn from our study are as follows. First, the relationship between the park's age and patent applications filed by tenants (the proxy of firm performance) follows a U-shape. Firms located in very new or longer established parks have more patents. Second, the relationship between the age of the park and tenants' sales follows an inverted U-shape. Firms in middle-aged parks show higher sales per worker. Finally, firms that have just moved into the park or young firms moving into the park perform better. We suggest that a government body should create different approaches for improving innovation and management performance to regenerate industrial parks.